Intra-islet glucagon secretion and action in the regulation of glucose homeostasis - Wang, Qinghua; Liang, Xinyun; Wang, Susanne (Frontiers in Physiology, 2013)
Glucagon, a key hormone in the regulation of glucose homeostasis, acts as a counter-regulatory hormone to insulin by promoting hepatic glucose output. Under normal conditions, insulin and glucagon operate in concert to maintain the glucose level within a narrow physiological range. In diabetes, however, while insulin secretion or action is insufficient, the production and secretion of glucagon are excessive, contributing to the development of diabetic hyperglycemia. Within an islet, intra-islet insulin, in cooperation with intra-islet GABA, suppresses glucagon secretion via direct modulation of -cell intracellular signaling pathways involving Akt activation, GABA receptor phosphorylation and the receptor plasma membrane translocation, while intra-islet glucagon plays an important role in modulating β-cell function and insulin secretion. Defects in the insulin-glucagon fine-tuning machinery may result in β-cell glucose incompetence, leading to unsuppressed glucagon secretion and subsequent hyperglycemia, which often occur under extreme conditions of glucose influx or efflux. Therefore, deciphering the precise molecular mechanisms underlying glucagon secretion and action will facilitate our understanding of glucagon physiology, in particular, its role in regulating islet β-cell function, and hence the mechanisms behind body glucose homeostasis.